Silver nanoparticles synthesized from Spilanthes acmella L. Murr extract using antifungal and antibacterial - Cao Tien, Khoa; Dinh Thuy, Van; Dang Thi, Huong; Phan Dinh, Quang; Do Thi, Hue (Communications in Physics, 2023)
Spilanthes acmella L. Murr is a medicinal herb with many valuable biological activities such as clearing heat, detoxifying, dissipating phlegm, antiseptic, pain relief, antifungal, anti-inflammatory... In this work, we used Spilanthes acmella L. Murr extract to synthesize silver nanoparticles to combine and enhance the activity of silver and Spilanthes acmella L. Murr extract in antibacterial and antifungal activities. The reaction parameters were investigated to find the most optimal conditions for synthesizing silver nanoparticles, such as AgNO3 volume, solution pH, and reaction temperature. UV-VIS absorption spectra were used to analyze the influence of the reaction parameters. The functional groups on the silver nanoparticles as well as the Spilanthes acmella L. Murr extract were found by infrared absorption (FTIR) spectroscopy. The crystal structure of the synthesized silver nanoparticles was determined by X-ray diffraction (XRD) spectroscopy. On the basis of the synthesized silver nanoparticles, the antifungal activity was investigated on the strains: A. flavus (Af), A. brasiliensis (Ab), C. Albicans (Ca), and antibacterial: Staphylococcus aureus (SA), Pseudomonas aeruginosa (PA) was performed to compare the activity of the antibiotic ampicillin 100 mg/mL.